Car Battery Power Monitoring and Prediction System Using Microcontroller Based Linear Regression Method - Rohman, Muhammad Hanif Rifki; Prabowo, Sidik; Nuha, Hilal Huda (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The accumulator is a device to storage for electrical energy in four-wheeled vehicles, requiring frequent maintenance and supervision therefore the battery can be used for a long time. Most of the drivers rarely check the age of the accumulator, this could lead the vehicle to fail to start the engine and this is usually caused by running out of power. This study aims to minimize the problems that are often faced by motorists, namely, running out of power suddenly which causes the car to be unable to run. In this study, predictions of battery power were carried out using the Arduino Uno microcontroller, the acs712 sensor as a battery voltage detector, and the python language to process data with linear regression methods. The system is evaluated based on the functionality and performance of the system. From the test result, it was found that the system functionality runs 100% according to its function. And the results of the prediction of power with the linear regression method can be done because linear regression gives an R2 of 0.88.